Education and Millennium Goals - Abd Razak, Dzulkifli (2009)
IF there were doubts that Malaysia was not putting a premium on education, the 17th Conference of Commonwealth Education Ministers (17CCEM) dismissed them. So, too, would be the case for the Commonwealth in general. The conference ended on an optimistically high note. Given the theme, "Education in the Commonwealth: Towards and beyond global goals and targets", it is not surprising that many have chosen the Millennium Development Goals (MDGs) as their reference points. We have barely another five years to see the successful completion of the MDGs. And unless this is persuasively achieved, there is no "beyond" to talk about.